Pochodne formy nabycia obywatelstwa oraz jego utrata w systemach prawnych Polski i Niemiec. Kwestia obywatelstwa kobiet zamężnych - Durczak, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The author of this article conducts analysis in order to compare methods and conditions of secondary acquisition as well as loss of Polish and German citizenship, including the situation of married women under nationality law in Poland and Germany. The article refers to constitutional acts, nationality acts and conventions ruled by international law. Moreover, the analysis is supported by Polish, German and international literature. While Poland and Germany are member states of the European Union and share links to legal tradition of the Ancient Rome, there are certain differences between nationality regulations legislated in these jurisdictions, especially with regard to cases of registered partnerships of the same sex and double citizenship.
Keywords: obywatelstwo; kobiety; Polska; Niemcy; prawo obywatelskie